Qaḍāyā Muʻāṣirah - Rusli Hasbi (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2005)
Among the problems of jurisprudence (fiqh) that are emerging nowadays is concerning the legal status of Misyar marriage and copyright. Misyar marriage is one kind of marriage that has the common purpose with the ordinary marriages. The difference is that a wife is not given their rights such as a place of living, spousal support, and en equal division as other wives. As for copyright, whether in the form of writing books, inventions or particular literary works is the rights of the owner, and is not permissible for anyone to steal this right. In this writing, the author seeks to put forward differences of opinions among the scholars on the following law of Misyar marriage and copyright.